Determination of additional access door location for a traditional house in Libya to reduce evacuation time - Mkharem, Mufida Ibrahim (2019)
Fire incidents involving traditional houses in Libya between the years 2011 to 2015 accounted for 3,562 cases, claimed 436 lives and 614 injuries. These are linked to the types of roofing materials used in the building of the traditional Libya houses. Estimated losses of USD 2,217,500 were associated with the types of roofing materials used in such houses which are mainly from the date Palm Tree (DPT) parts, the harsh adverse weather impact, high fire load of consumables, poor fire-safety awareness and knowledge amongst the occupants. In order to minimize these negative impact on the house occupants based on some structural limitation of the existing emergency doors access and inadequate corridor width of 1 meter. This research study focuses on the determination of additional new door location on the existing traditional Libya house for the reduction of safe egress evacuation time in case of house fire eruption. This research study focused first on four-laboratory thermal characterization test on applied DPT building materials samples. Secondly, the mimic fire simulation modelling of a prototype traditional Libya house with the adoption of appropriate validated experimental data as inputs for the fire eruption study using Pyrosim Fire Simulator (PFS) Software. This mimic fire eruption model was produced close to reality with varying fire source Heat Release Rate per Unit Area (HRRPUA), and control air ventilation impact. Thirdly, egress safe evacuation analysis studies of 5, 10 and 15 occupants at different location of the same Pyrosim building fire model executed in Pathfinder Software (PS) with the new determined door location for improved egress evacuation time reduction. The roofing material characterization result produced the highest fire load calorific value contribution of 4,107.2 cal/g, thermal conductivity value of 0.189 W/m ⁰C and heat diffusivity rate value of 0.128 mm/s as adopted input parameters for the mimic Pyrosim simulation. The fire simulation sources from children bedroom indicated that the room temperature increases with increase in the HRRPUA from available fire load contents, with highest measured values of 896 ⁰C for winter and 859 ⁰C for summer season open door fire, based on the external air support for enhanced rate of fire growth, and heat spread. The negative impact of occupant density variation (10 – 15 persons) is eliminated with the same improved egress evacuation time of 7.6 s and 14.4 s for running and walking speed respective across all house densities above 5 persons with the additional new door location. Hence, produced an improved saved evacuation time margin of 1.6 s and 2.6 s for walking and running speed respectively. This is due to the reduction in the traveling distance covered with the new additional door location during egress safe evacuation. The analyzed questionnaire result indicated that larger numbers of Libyan house occupant have poor awareness of fire safety activities and limited knowledge on safe egress evacuation in case of unwanted fire eruption, despite good knowledge of fire hazards and consequences. This study has divulged detail insight into the fire accident in traditional Libya houses as a base for future in-depth study, and eliminate the negative impact of long evacuation time due to inadequate access provision for egress safe evacuation. The needed training requirement is also provided from the analyzed questionnaire for adequate training of all occupant appropriately.